Assessing the Environmental Impact of Layer Chicken Farming: Sustainable Islamic Business Ethics: Dampak Lingkungan Budidaya Ayam Petelur: Etika Bisnis Islam Berkelanjutan - Aswar, Muhammad Asrul; Arif, Usman; Kurniawan, Chandra; Nur, Sausan; Aprilia, Aura Nur; Pramudita, Oktavia Dwi (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2024)
Abstract: This study explores the environmental impacts of layer chicken farming from an Islamic studies perspective, with particular attention to Islamic business ethics and Qur’anic interpretations related to environmental conservation. While layer farming contributes to economic and social development, it also poses notable environmental challenges. Adopting a Qur’anic interpretive framework based on Tafsir al-Mishbah by Quraish Shihab, this research focuses on the farming practices of a company named UD. Berkah Telur in Madiun. Employing a qualitative descriptive method, data were obtained through interviews and a review of relevant literature. The findings indicate that UD. Berkah endeavors to uphold the principles of Islamic business ethics, particularly regarding animal welfare and product quality. Nevertheless, challenges remain in fully integrating sustainable Islamic economic principles into all operational aspects. Despite these limitations, the enterprise demonstrates a clear commitment to social and environmental responsibility adhering Islamic teachings. As interpreted through Tafsir al-Mishbah, Islamic business ethics emphasize a vision of sustainability that extends beyond short-term profit orientation to include the preservation of the environment for future generations. Abstrak: Penelitian ini mengkaji dampak lingkungan dari budidaya ayam petelur dalam perspektif studi Islam, dengan menitikberatkan pada etika bisnis Islam dan interpretasi ayat-ayat Al-Qur'an terkait pelestarian lingkungan. Budidaya ayam petelur, meskipun memberikan manfaat ekonomi dan sosial, juga menimbulkan dampak lingkungan yang signifikan. Studi ini menggunakan pendekatan tafsir Al-Qur'an dari Tafsir Al-Mishbah karya Quraish Shihab, dengan fokus pada praktik budidaya oleh UD. Berkah Telur di Madiun. Penelitian ini bersifat kualitatif-deskriptif, mengumpulkan data melalui wawancara dan kajian literatur yang relevan. Hasil penelitian menunjukkan bahwa UD. Berkah Telur berusaha menerapkan prinsip etika bisnis Islam, terutama dalam hal kesejahteraan ternak dan kualitas produk yang sehat. Namun, masih ada tantangan dalam menerapkan prinsip ekonomi Islam yang berkelanjutan di seluruh aspek operasional. Meskipun demikian, usaha ini telah menunjukkan komitmen terhadap tanggung jawab sosial dan lingkungan sesuai ajaran Islam. Etika bisnis Islam, sebagaimana diinterpretasikan melalui Tafsir Al-Mishbah, menggarisbawahi pentingnya visi keberlanjutan yang tidak hanya berorientasi pada keuntungan jangka pendek tetapi juga pada pelestarian lingkungan untuk masa depan.